CRISTA: um apoio computacional para atividades de inspeção e compreensão de código - Porto, Daniel de Paula (Universidade Federal de São Carlos, 2009)
Software inspection is a key activity of software quality assurance that can be applied in the whole development process since it is a static activity essentially based on reading. Depending on the artifact that is being inspected, we need to apply the appropriated reading technique. Stepwise Abstraction (SA) is a reading technique commonly used in code inspections. However, its application is laborious and time consuming. Aiming to help and facilitate the application of SA, this work presents CRISTA (Code Reading Implemented with Stepwise Abstraction), a tool to support SA-based inspection processes. This tool uses a visual metaphor to facilitate code navigation and has several resources to help program understanding and documentation. Due to these resources, CRISTA is also helpful for reverse engineering, re-engineering and maintenance activities. Three experimental studies were carried out to get feedback on the tool usability and usefulness for inspections and maintenance activities. The results provide insights that CRISTA is easy to use and adequately supports the inspection process as well as code reading by Stepwise Abstraction. Besides, in the context of maintenance, its resources make this activity less time-consuming.
Keywords: Engenharia de software; Inspeção de software; Visualização de software; Compreensão de dados; Manutenção de programas; Engenharia reversa; Code Inspection; Stepwise abstraction; Software visualization; Code comprehension; Maintenance; Reverse Engineering; Re-engineering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA